Heavy metal and bacterial contamination in “Etak” (Corbicula fluminea) tissue selling in Kelantan, Malaysia - Dee, Koh Han (2019)
The freshwater clam, Corbicula fluminea is one of the sources of income and has become a renowned traditional food in Kelantan, Malaysia. However, C. fluminea is categorized as filter feeder which accumulates heavy metals and bacteria from contaminated river or water stream into its soft tissue. As the river contamination continues to increase at an alarming rate, coupled with the unhygienic handling of sellers at smoked and selling stage, this clam is suspected to be contaminated. Furthermore, the heavy metals and bacterial population in the soft tissue of C. fluminea have not been clarified. In this research, the contamination of C. fluminea was identified in forms of heavy metal and bacteria. The heavy metal analysis (Cd, Cr, Cu, Mn, Pb and Zn) has been carried out using acid digestion and identified by using atomic absorption spectrometer. Meanwhile, the bacteria communities were identified by their 16S rRNA gene of bacterial DNA of C. fluminea. The experimental results reveal that there were no significant differences among the stages in term of heavy metals contamination. The results show that the heavy metals concentrations (μg/g) in the soft tissue of C. fluminea were at different levels for fresh stage (Cd: 1.15±0.17 μg/g, Cr: 3.52±2.43 μg/g, Cu: 34.26±19.72 μg/g, Mn: 57.92±42.48 μg/g, Pb: 2.88±1.51 μg/g and Zn:111.93±49.06 μg/g), smoked stage (Cd: 1.23±0.22 μg/g, Cr: 3.44±1.35 μg/g, Cu: 29.00±21.23 μg/g, Mn: 57.58±35.64 μg/g, Pb: 2.48±1.47 μg/g and Zn: 94.52±32.14 μg/g) and selling stage(Cd: 1.22±0.19 μg/g, Cr: 3.63±1.58 μg/g, Cu: 26.49±12.37 μg/g, Mn: 53.97±29.01 μg/g, Pb: 3.26±1.81 μg/g and Zn: 91.94±39.12 μg/g). The results obtained were compared with the maximum permissible limits set by Malaysia Food Regulations (1985) (Cd: 1.0 μg/g, Cu: 30.0 μg/g, Pb: 2 μg/g and Zn: 100.0 μg/g) and FAO/WHO (1984) (Cr: 13 μg/g and Mn: 5.4 μg/g). It was found that Cd, Mn and Pb concentrations were exceeding the permissible limits. Regarding bacterial contamination, Proteobacteria (87.8%), Firmicutes (8%) and Bacteroidetes (3.1%) were the most dominant groups at phylum level, while Aeromonas (47%), Klebsiella (15.7%) and Enterobacter (10.1%) were predominant at genus level. High levels of Cd, Mn, Pb and pathogen in C. fluminea shows that it is not safe for regular consumption. In conclusion, this study has successfully determined the concentration of heavy metals and identified the bacterial community in C. fluminea.